2009
DOI: 10.1002/hrm.20267
|View full text |Cite
|
Sign up to set email alerts
|

Problem‐focused versus emotion‐focused coping strategies and repatriation adjustment

Abstract: Failure to cope with a stressful repatriation transition can derail the global career experience. Repatriate stress-coping behaviors have not been examined empirically, however. This study explores the factor structure of an extensive array of coping strategies and their relation with repatriate adjustment. Data collected from 282 repatriates involved in a boundaryless repatriation experience reveal a factor structure consistent with problem-and emotion-focused dimensions documented elsewhere. Regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 82 publications
6
70
0
4
Order By: Relevance
“…Problem-focused strategies have been inversely related to psychological and physiological stress symptoms. For example, in a study of 282 individuals who had repatriated from Japan (primarily currently living in the U.S.), emotionfocused coping strategies were negatively related to general, social, and work adjustment, whereas problem-focused coping strategies were positively related to adjustment (Herman & Tetrick, 2009). A similar pattern of results was noted in a sample of Westerners adjusting to life in different countries for their business roles (Selmer, 2001).…”
Section: Problem-focused Vs Emotion-focused Copingmentioning
confidence: 64%
“…Problem-focused strategies have been inversely related to psychological and physiological stress symptoms. For example, in a study of 282 individuals who had repatriated from Japan (primarily currently living in the U.S.), emotionfocused coping strategies were negatively related to general, social, and work adjustment, whereas problem-focused coping strategies were positively related to adjustment (Herman & Tetrick, 2009). A similar pattern of results was noted in a sample of Westerners adjusting to life in different countries for their business roles (Selmer, 2001).…”
Section: Problem-focused Vs Emotion-focused Copingmentioning
confidence: 64%
“…In this regard, many researchers have stated that coping styles play a significant role in students' ability to manage stress (Aldwin, 2004;Cross, 1995). Studies on freshmen in particular (Dyson & Renk, 2006;Gardner, Krägeloh, & Henning, 2014;Herman & Tetrick, 2009;Yalım, 2007;Yiqun, Yueqin, & Yiwen, 2010) have indicated that while some coping styles positively contributed to university adjustment, others just rendered the process more difficult. For instance, Brissette, Scheier, and Carver (2002) found that students' ability to adjust to their university increased as positive reinterpretation, a coping style, increased.…”
mentioning
confidence: 99%
“…At the same time, frequent international travel is a cause for stress and may accelerate resultant burnout and personal and family difficulties (Westman, Etzion, & Gattenio, 2008). Stress has been identified as one of the factors that influence a repatriate's ability to cope with readjustment upon return (Herman & Tetrick, 2009). …”
Section: Expatriation and Repatriation Research Evolution Over Timementioning
confidence: 99%